2015
DOI: 10.1016/j.polymer.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of functional poly(amino ester sulfide)s and utility in delivering pDNA and siRNA

Abstract: The development of efficacious carriers is an important long-standing challenge in gene therapy. In the past few decades, tremendous progress has been made toward non-viral vectors for gene delivery including cationic lipids and polymers. However, there continues to be a need for clinically translatable polymer-based delivery carriers because they offer tunable degradation profiles and functional groups, diverse structures/morphologies, and scalability in preparation. Herein, we developed a library of 144 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…[32][33][34][35][36] It is worth noting that this mini review has focused exclu-sively on ROP of lactones and the resulting functional polyesters. Reports of functional polymers via step-growth polymerization, [37][38][39][40][41][42] amino functional polycarbonates, [43][44][45][46] and functional lactide derivatives 47,48 have greatly contributed to the field of drug and gene delivery.…”
Section: Scheme 7 Derivatization Of Pcl By Combining Rop and 'Click' Chemistrymentioning
confidence: 99%
“…[32][33][34][35][36] It is worth noting that this mini review has focused exclu-sively on ROP of lactones and the resulting functional polyesters. Reports of functional polymers via step-growth polymerization, [37][38][39][40][41][42] amino functional polycarbonates, [43][44][45][46] and functional lactide derivatives 47,48 have greatly contributed to the field of drug and gene delivery.…”
Section: Scheme 7 Derivatization Of Pcl By Combining Rop and 'Click' Chemistrymentioning
confidence: 99%
“…The section starts with Fossum's paper [50] which provides examples of reactivity ratio-controlled polycondensation reactions and their use in the synthesis of functional polyethers. In his paper, Siegwart [51] demonstrates the utility of sequential thiobutyrolactone aminolysis and thiol-ene reactions in the preparation of biodegradable polymers with applications in nucleic acid delivery. Peng's paper [52] describes novel aluminum complexes that mediate stereoselective ring-opening polymerizations.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…For TK-RNAi to be effective in insects, the dsRNA should be at least 60 bp in length (Bolognesi et al, 2012;Li et al, 2015) and delivered in high quantity (Bally et al, 2018;Mamta and Rajam, 2017). This has been accomplished by expressing dsRNA guided by strong nuclear promoters (Baum et al, 2007;Yan et al, 2015) or from the chloroplast genome (Bally et al, 2016;Jin et al, 2015;Zhang et al, 2015). Recent studies have shown that dsRNA expressed in the chloroplast evades degradation by plant RNAi, accumulates to high levels and can confer protection against the cotton bollworm, Helicoverpa armigera, and the Colorado potato beetle, Leptinotarsa decemlineata (Bally et al, 2016;Jin et al, 2015;Zhang et al, 2015), in tobacco and potato, respectively.…”
Section: Introductionmentioning
confidence: 99%